Monitoring of metabolic variables in children and adolescents who use atypical antipsychotics assisted at the Pereira Rossell Pediatric Hospital Center (Archives of Pediatrics of Uruguay, 2025)
Introduction: the consumption of psychotropic drugs, particularly antipsychotics, has been increasing globally in children and adolescents (NNA). In our country, there are few studies on the subject, but they show a high level of use of these drugs. Atypical antipsychotics are associated with metabolic alterations such as dyslipidemia, diabetes, and overweight/obesity, among others.Objectives: describe clinical and paraclinical metabolic variables in NNA using atypical antipsychotics, admitted to moderate care wards at the Pereira Rossell Hospital Center, during the period of July - September 2022.Methodology: an observational, cross-sectional, descriptive study was conducted, including patients aged 2-15 years. Pharmacological, anthropometric, and biochemical data were obtained. Physical activity and dietary quality were evaluated. The PSPP statistical software version 3 was used. The study was approved by the Research Ethics Committee of the Pereira Rossell Hospital Center (CHPR).Results: fifty-three NNA were included, with a median age of 13 years. Risperidone, quetiapine, and aripiprazol were the most commonly used. Thirty percent presented overweight/obesity, 50% were sedentary, and 30% had unhealthy eating habits. Twenty-one NNA had had the recommended blood biochemichal tests used to monitor these drug users.Conclusions: metabolic alterations were found in more than half of the included subjects. Risperidone remains the most prescribed antipsychotic in this population, with a growing use of aripiprazol. Polypharmacy persisted as a prescription problem in these patients.
Keywords: Antipsychotic Agents; Child; Adolescent